Culturally Relevant STEM (CReST): An Integrated Support Curriculum for High School Chemistry and World History - James K. Ferri; Rachel Sparks White (MDPI AG, 2024)
Convergence education, driven by compelling or complex socio-scientific problems, is an approach to bring cultural relevance into secondary STEM education. National trends show the need to increase the STEM workforce by leveraging educational research and innovative practices within the secondary level to increase student interest prior to graduating high school. We introduced CReST (Culturally Relevant STEM) in a US high school pilot study. Student participants included 276 Chemistry students and 19 World History I students. The study also engaged four (4) high school teachers in chemistry and social studies with the challenge of cultural heritage conservation through the lens of the (physicochemical) life cycle of mural paintings in Europe. Teachers were provided with (1) professional development; (2) a digital curriculum; and (3) modular kits for hands-on learning. The research focused qualitatively on the experiences from the teacher and students as well as quantitatively to assess whether there was an increase in student academic performance. We found a statistically significant gain with respect to Chemistry (4.0%) and World History (13.4%) content. Students and teachers responded with overwhelming positivity in individual and focus-group interviews. This amplifies the further need of convergent educational approaches in high school STEM education to enhance engagement and increase student learning.